KONTRIBUSI PENDIDIKAN ISLAM TERHADAP PENDIDIKAN NASIONAL - Ruslan Ruslan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2017)
The Indonesian nation that is expected to be born from the national education system is a nation that is intelligent intellectual, moral, and charitable. Delegating the overall responsibility of these intelligent factors to national education is almost impossible. Therefore, the presence of Islamic education in Indonesia becomes urgent, especially in developing a morally intelligent Indonesian nation and charity. The existence of Islamic education as a force that contributes to the life of nation and state. Islamic education occupies a very important position and can not be separated in building the nation of Indonesia as a whole. Islamic education is the main element of forming the character and morals of the nation. Islamic education plays an important role in shaping religious values ​​and morals in social life. Integrating the two educational systems, will strengthen the spirit of realizing national ideals. Thus, both educational systems (Islamic education and national education) should be equally positioned in building a nation and not in a separate position much less dichotomistic.